Workshop Value and Valuation - Borges, V. (Workshop Value and Valuation ISCTE. Org. Luísa Veloso, 2023)
Making a name grant-flipping across Europe: A study of Portuguese artists by FCG Vera Borges CIES-Iscte vera.borges@iscte-iul.pt This paper describes how artists “make a name” for themselves by “flipping” from one grant, funding, or project to another between Portugal and other European countries. Deploying Menger’s conceptualization about talent and inequalities and bringing together the arts and science through the contributions by Karpik, Podolny, and Simonton, and recent frameworks on cultural consecration, we propose to analyse value in arts as a multidimensional concept with a constellation of dimensions of analysis. This is common in fields where judgement criteria are ambiguous and multiple key players hold stakes. The paper examines data from the Calouste Gulbenkian Foundation Study (2022): an online survey of artists (N = 488) and qualitative interviews (N = 60). The study combined several indicators – countries where the artists studied, where they currently work; attended schools, awards, employing institutions, income, and contracts - to suggest that “creating value” implies concentrating on the same individual multiple supports, which protect the creativity, originality, constant learning, and demonstrate evidence about the value of artistic work. The paper furthermore discuss how artists can create value when constantly under funding pressures, the evaluation and politics of art remain opaque, institutions are fragile, and, in certain artistic domains, audiences are almost absent. Moreover, the compromised roles of artists within art institutions obscures their opposed values. How can works of art be recognized when the institutional conditions within which they are exhibited are compromised and exploited? The paper also contends that, in accord with the principles of art worlds, the development of these fields has required artists produce ever more demonstrations of their social relevance to local communities. The study argues that funding and private support for the art world in Portugal serve not only to raise technical competences of individuals but also to enlarge their professional opportunity networks within a strongly vocational and competitive labor market. The study underpins the conclusion that arts funding has more than ever provided a generation of virtuoso artists with promising positions and careers. First, through their technical performances, learned in the most famous European schools or through working in orchestras and European cultural institutions, capable of proposing another model of value. Secondly, in searching and being part of European networks, some artists become winners while others are losers, vivem à tona, and might be pursuing their ambitions while simultaneously proffering themselves as retainers at the foot of a pyramid that sustains a longstanding art world principle, the ethos of precarity.